2001
DOI: 10.1075/eoc.4.2.05bro
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vocal output by chimpanzees finding food in the presence or absence of an audience

Abstract: Chimpanzees (Pan troglodytes) give both food barks and pant hoots upon encountering food and regulate their calls based upon such factors as food quantity, quality, and possibly divisibility. Although it has been determined that several species, both primate and non-primate, regulate their food calls based upon the presence or absence of an audience, this has not been systematically explored with chimpanzees. Group-housed chimpanzees were given access to either large or small quantities of food when they had e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 19 publications
0
28
0
2
Order By: Relevance
“…In previous studies on chimpanzees, changes in the rates of production of specific vocalizations were altered by parameters associated with either food quantity or divisibility (Hauser, Teixidor, Field, & Flaherty 1993) as well as the absence or presence of a social partner (Brosnan & de Waal 2003). In contrast, rather than alter the calling rate of a specific vocalization in response to the presence or absence of an audience, the results reported here indicate the chimpanzees produce different vocalizations depending on the presence or absence of a human in association with a food item.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on chimpanzees, changes in the rates of production of specific vocalizations were altered by parameters associated with either food quantity or divisibility (Hauser, Teixidor, Field, & Flaherty 1993) as well as the absence or presence of a social partner (Brosnan & de Waal 2003). In contrast, rather than alter the calling rate of a specific vocalization in response to the presence or absence of an audience, the results reported here indicate the chimpanzees produce different vocalizations depending on the presence or absence of a human in association with a food item.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on chimpanzees, for instance with Mitani and Nishida [1993] noting that high‐ranking chimpanzees produce more pant hoots when alliance partners are nearby. Brosnan and de Waal [2005] have described somewhat more complex effects for chimpanzee food calls, with the presence of a visible audience associated with increased vocalizing when large food quantities were discovered, but with decreased calling when only a small amount of food was found. An analogous outcome has been reported in wild chimpanzees, who vocalize much less than expected when raiding the abundant food found in agricultural fields [Wilson et al, 2007].…”
Section: Evaluating Evidence Of Vocal Flexibilitymentioning
confidence: 99%
“…For instance, several species adjust their food calling depending upon both the social environment and the quantity or divisibility of available food (Caine et al, 1995;Chapman and Lefebvre, 1990;Elgar, 1986;Evans and Marler, 1994;Hauser et al, 1993;van Krunkelsven et al, 1996). In one study, it was found that individuals suppressed calls for a small, unshareable amount of food but did not for a larger amount of food (15 apples) that presumably could not have been consumed before the food possessor was discovered by the group (Brosnan and de Waal, 2003b). In another study, unrelated to food calling, capuchin monkeys adjusted their willingness to participate in a cooperative task dependent upon the food distribution.…”
Section: The Effect Of Hierarchies and Dominance On The Sense Of Fairmentioning
confidence: 99%
“…Although one test is insufficient to understand all of the contingencies of how relationships affect responses to inequity, it is interesting that individuals who had grown up together and had social interactions implying harmony showed communal orientation to the IT while those from the less stable situations showed more contingent rules. Furthermore, it is known that chimpanzees will alter their behavior depending upon the current social situation (Brosnan and de Waal, 2003b), their housing situation (Aureli et al, 1997;Baker et al, 2000), or their social group (Whiten et al, 1999). However, due to the scarcity of chimpanzees most behavioral testing utilizes individuals from only a single social group (or chimpanzees from pair-or single-housed situations).…”
Section: Social Effects On the Inequity Responsementioning
confidence: 99%